Architecture as Setting the Stage: A framework for architectural design of virtual reality places centering the concept of presence through Wideström, Hernandez-Ibañez and Barneche-Naya, and Slater - Won, Meghan (University of Waterloo, 2024)
Architecture shapes our physical world – and it shapes our virtual worlds as well. Virtual architecture creates the place in which a participant in Virtual Reality (VR) can understand and be immersed in the VR experience. This research contributes a framework for conceptualizing how architecture can work in service of immersive VR experiences that evoke a feeling of presence in the participant. Presence is the sensation of “being there” in a mediated environment through the allocation of attentional resources perceived physically and psychologically. It is the authentic feeling of being in a world other than the one in which one is physically located – the ultimate goal for a heightened VR experience. Architecture as Setting the Stage highlights presence felt in a VR experience as the benchmark for a successful virtual space. The framework synthesizes the concepts of Wideström’s Stage, Hernandez-Ibañez and Barneche-Naya’s Virtual Utilitas, and Slater’s Place Illusion, centering presence within each. This research is prompted by powerful VR experiences that evoked presence in myself - like the cave setting in Scanner Sombre and the depictions of home in The Book of Distance. The latter VR project, The Book of Distance created by Randall Okita, is used as a case study in analysing how architecture supports engagement and connection between the participant and the virtual spaces. The concept of Stage, from the philosophical dissertation of A Seeing Place (2022) by researcher and lecturer Josef Wideström, provides language and philosophy in conceptualizing the relationship between the physical and the virtual. The metaphor of Stage positions virtual space as a stage, connecting concepts of how we understand theatre to how we understand VR. Stage highlights how audiences in theater and participants in VR negotiate their understanding of representations, whether physical or virtual, leading to agreements about their meaning and context. This research extends his metaphor of Stage into the language of architectural design. Hernandez-Ibañez and Barneche-Naya’s framework Virtualitas from their conference paper Cyberarchitecture (2012) addresses the need for the analysis and translation of established architectural theory into the realm of virtual architecture, enabling architects to approach virtual design with the same depth of consideration as physical practice. The concept of Virtualitas redefines the traditional architectural Vitruvian Triad - firmitas, utilitas, and venustas - to encompass virtual architecture’s broader considerations beyond aesthetics. Their contemporary framework informs the concept of Virtual Utilitas in this research, which centers presence as a key condition in VR architecture achieving Virtual Utilitas. Researcher and psychologist Mel Slater’s established concept of Place Illusion (2005, 2022) offers psychological insight into how the construction of virtual spaces are perceived, and its influence on achieving presence. Place Illusion describes the influence of the coherent and convincing creation of place on a participant in a VR experience. Architecture as Setting the Stage works as a conceptual bridge in understanding the properties of virtual architecture and informs three propositions of how architecture influences a participant; directing attention, relational meaning, and expression of boundaries. The propositions speculate how virtual architecture through design impacts presence. The framework and propositions are then applied to a VR experience case study, The Book of Distance (2020) by Randall Okita and the National Film Board of Canada. The Book of Distance is investigated through a first-person written account of observations and reactions to the experience. This descriptive passage aims to portray an authentic experience in VR. The passage is then followed by an analysis of the experience through the propositions informed by Architecture as Setting the Stage. VR holds exciting potential for defining new experiences that go beyond those constrained by our physical world. Architectural knowledge, when adapted and applied to a virtual context, plays a significant role to the creation of VR experiences. Architects must confront the complexities of VR through a language for common understanding and help shape our virtual worlds.
Keywords: virtual reality; new media; virtual architecture; virtual space; architectural theory; framework for design; presence; stage; Widestrom; Slater; Hernandez-Ibañez; Barneche-Naya; place making; VR